-10=-3t+2

Simple and best practice solution for -10=-3t+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=-3t+2 equation:



-10=-3t+2
We move all terms to the left:
-10-(-3t+2)=0
We get rid of parentheses
3t-2-10=0
We add all the numbers together, and all the variables
3t-12=0
We move all terms containing t to the left, all other terms to the right
3t=12
t=12/3
t=4

See similar equations:

| 8x+3x+3-2=90 | | 16-7x=5x-8 | | X+1-3x=9 | | 1/2(4y-8)=4 | | 5x+3(x-4)=8x-15 | | 2(3x−4)=3+6x | | 4x+10=46-2x | | 2(3x−4)=3+6x. | | 6x-8(2x-4)=46 | | -4-6x=6(3-x)-5x | | 5x10+10=3x-12 | | 9m+10=46 | | -14+6=-2(x+6) | | 5=6(y-2)-1 | | 12m-27=7m+43 | | 17+4=-3(2x-7) | | 4x+1.4=6.2 | | 4x-17=-11 | | 9x-8=5x-10 | | 2.3=(t-1.8)/2 | | -6(n-6)=12 | | x/5+x/8=13/14 | | 4(2x+9)=-40+44 | | 3n+1=-6-4n | | 5x–45=–10 | | -4(v-75)=-48 | | 2(t−5)=48 | | 6x+3=5x–20 | | 40=5(d-72) | | X+6÷3=2x÷4 | | -36=-6(f-78) | | 9(m−3)+3m=7m+43 |

Equations solver categories